The Effectiveness of the Independent Curriculum Implementation in Improving the Quality of Learning and Strengthening Student Character at SMA Negeri 1 Paiton - Izzatul Afidah; Moh. Rifiki (Academicus: Journal of Teaching and Learning, 2026)
The shift in educational paradigms has encouraged schools to implement the Independent Curriculum to create more flexible, student-centered learning and support competency and character building. However, most research still focuses on technical implementation aspects, thus not comprehensively examining its effectiveness on the quality of learning and strengthening student character at the senior high school level. This study aims to analyze the effectiveness of the Independent Curriculum implementation in improving the quality of learning and strengthening student character at Paiton 1 Public High School. The study used a qualitative approach with a case study type. Data were collected through observation, interviews, and documentation of informants selected using a purposive sampling technique, consisting of the principal, vice principal, teachers, and students. Data analysis used the Miles, Huberman, and Saldana model. The results of the study indicate that the implementation of the Independent Curriculum creates more flexible, participatory, and student-centered learning through differentiated learning, diagnostic assessment, formative assessment, and student-centered learning. The implementation of the Pancasila Student Profile Strengthening Project (P5) also contributes to strengthening student character. The novelty of this research lies in the analysis that integrates the quality of learning and strengthening of student character through the perspectives of various informants, thus providing a more comprehensive picture of the effectiveness of the implementation of the Independent Curriculum in senior high schools.